Cycloaddition of CO2 with epoxides into cyclic carbonates catalyzed by a binary organocatalyst under mild conditions - Wen-Wang, Yu; Xiang-Guang Meng; Zi-Yu, Gan; Li, Wen; Yu-Lian, Zhang; Zhou, Jie (Catalysis science & technology, 2024)
Fixing CO2 into value-added cyclic carbonates is an effective way to reduce CO2 emissions. A metal-free and solvent-free catalytic system has been developed for the cycloaddition of CO2 with epoxides into corresponding cyclic carbonates. The catalytic system can in situ catalyze the conversion of CO2 into cyclic carbonates from actual flue gas under atmospheric pressure with a carbonate yield of up to 99.4%. The water resistance experiment and catalytic mechanism were investigated in detail. A ten-fold amplification reaction was conducted at 70 °C and atmospheric pressure, and the residual CO2 in the flue gas decreased to 985 ppm, indicating that the CO2 in the flue gas was effectively captured and removed under very mild conditions. This work provides a feasible approach for in situ capture and conversion of CO2 in flue gas at atmospheric pressure.